A longitudinal study of humpback whales in Irish waters. (9th January 2015) - Ryan, Conor; Whooley, Pádraig; Berrow, Simon D.; Barnes, Colin; Massett, Nick; Strietman, Wouter J.; Broms, Fredrik; Stevick, Peter T.; Fernald, Thomas W.; Schmidt, Christian
Abstract : Knowledge on the ecology of humpback whales in the eastern North Atlantic is lacking by comparison with most other ocean basins. Humpback whales were historically over-exploited in the region and are still found in low relative abundances. This, coupled with their large range makes them difficult to study. With the aim of informing more effective conservation measures in Ireland, the Irish Whale and Dolphin Group began recording sightings and images suitable for photo-identification of humpback whales from Irish waters in 1999. Validated records submitted by members of the public and data from dedicated surveys were analysed to form a longitudinal study of individually recognizable humpback whales. The distribution, relative abundance and seasonality of humpback whale sighting records are presented, revealing discrete important areas for humpback whales in Irish coastal waters. An annual easterly movement of humpback whales along the southern coast of Ireland is documented, mirroring that of their preferred prey: herring and sprat. Photo-identification images were compared with others collected throughout the North Atlantic (N = 8016), resulting in matches of two individuals between Ireland and Iceland, Norway and the Netherlands but no matches to known breeding grounds (Cape Verde and West Indies). This study demonstrates that combining public records with dedicated survey data is an effective approach to studying low-density, threatened migratory species over temporal and spatial scales that are relevant to conservation and management.